2009
DOI: 10.1007/s12576-009-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting SOCE activation in mammalian skeletal muscle fibers

Abstract: Enzymatically dissociated mouse FDB muscle fibers, loaded with Fura-2 AM, were used to study the effect of mitochondrial uncoupling on the capacitative Ca(2+) entry, SOCE. Sarcoplasmic reticulum (SR) Ca(2+) stores were depleted by repetitive exposures to high K(+) or 4-chloro-m-Cresol (4-CmC) in the absence of extracellular Ca(2+). SR Ca(2+) store replenishment was substantially reduced using 5 microM cyclopiazonic acid (CPA). Readmission of external Ca(2+) (5 mM) increased basal [Ca(2+)](i) under two modaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Thus, at the normal resting membrane potential, the store-dependent Ca 2+ influx is around 20 μM s −1 (relative to cytoplasmic volume [35]). This is consistent with the readdition of 2 mM of external Ca 2+ to the Ca 2+ -depleted intact fibres refilling the SR in 1 to 2 min [10,27,30], therefore accumulating ∼1 mM of Ca 2+ [25] in this period. It should be noted that the store-dependent Ca 2+ influx rate will slow with SOCE deactivation, which is dependent on SR refilling rate [14,22].…”
Section: Properties Of Soce In Skeletal Musclesupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, at the normal resting membrane potential, the store-dependent Ca 2+ influx is around 20 μM s −1 (relative to cytoplasmic volume [35]). This is consistent with the readdition of 2 mM of external Ca 2+ to the Ca 2+ -depleted intact fibres refilling the SR in 1 to 2 min [10,27,30], therefore accumulating ∼1 mM of Ca 2+ [25] in this period. It should be noted that the store-dependent Ca 2+ influx rate will slow with SOCE deactivation, which is dependent on SR refilling rate [14,22].…”
Section: Properties Of Soce In Skeletal Musclesupporting
confidence: 86%
“…Following SOCE deactivation (when STIM1 is occupied by Ca 2+ , at low [Ca 2+ ] SR ), the SR Ca 2+ pump continues to load Ca 2+ into SR from the cytoplasm. Consistent with this is the low-amplitude transient increase in [Ca 2+ ] cyto due to store-dependent Ca 2+ entry into a Ca 2+ -depleted intact fibre in the absence of an SR Ca 2+ pump blocker and the continuous presence of 2-mM extracellular Ca 2+ [10,27].…”
Section: Properties Of Soce In Skeletal Musclementioning
confidence: 73%
“…Lack of ATP impairs plasma membrane potential (Na + /K + ‐ATPase is affected), having impact on NCX activity. Recent findings demonstrate that SOCE is inhibited by mitochondrial uncouplers [Bolanos et al, 2009]. Furthermore, it has been shown that SOC and NCX activities depend on each other.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that SOC and NCX activities depend on each other. Na + entry through the SOCE pathway leads to activation of the reversal of Na + /Ca 2+ exchanger activity [Harper and Sage, 2007; Bolanos et al, 2009]. Moreover, NCX associates with F‐actin through its central hydrophilic domain [Conrdrescu and Reeves, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that SOCE even contributes to mitochondrial Ca 2+ movements in skeletal muscle. 72 , 176 In short, it seems that the role of extracellular Ca 2+ entry such as SOCE fine tunes every function of skeletal muscle.…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%